Effective Learning Strategies in Improving Elementary School Students' Character: A Systematic Literature Review - Junaidi, Junaidi; Rohmani, Rohmani (International Journal of Multidisciplinary Approach Research and Science, 2024)
Character education plays a crucial role in shaping the quality personality of elementary school students. Effective learning strategies have been identified as a key approach to enhancing students' characters through education. These strategies help students understand and internalize the desired character values in their daily lives. This study aims to conduct a systematic literature review on effective learning strategies to enhance the characters of elementary school students. The methodology used is Systematic Literature Review (SLR), the data analysis approach is content analysis, and the database from Google Scholar or Google Scholar in the last three years (2020-2023) is analyzed. The results of this research obtained a database with the keywords "learning strategies" AND "student character" AND "elementary school students," from which 9 articles that met the inclusion criteria were selected and analyzed. The analysis concluded that adaptive, collaborative, and innovative learning strategies are key to ensuring the continuous development of students' characters. The role of teachers greatly influences the characters of elementary school students. The results of this research provide recommendations to elementary school teachers to adapt various learning strategies to effectively develop positive character traits in students for the future.